Studi Komparatif Perhitungan Anggaran Biaya dengan Building Information Modelling (BIM) 5D pada Pembangunan Gedung Sistem Administrasi Manunggal Satu Atap Kepolisian Daerah Kalimantan Timur - Putri Arlisdyawati Agustina Amini; Reno Pratiwi; Fachruddin Harami (Universitas Batanghari Jambi, 2026)
In the construction industry, the accuracy of volume calculations and cost estimation is a crucial factor in ensuring project efficiency and quality. However, many projects in Indonesia still use conventional methods such as AutoCAD and Microsoft Excel, which are not integrated and prone to input errors and cost overruns. Along with technological advancements, Building Information Modelling (BIM) has emerged as an innovative solution capable of integrating all project data into a single digital model that can be updated in real time. This study aims to compare cost estimation results between the conventional method and the 5D BIM method using Autodesk Revit software on reinforced concrete structural works for the construction of the One-Stop Administration System (SAMSAT) Building of the East Kalimantan Regional Police, as well as to analyze the level of efficiency achieved. The research employs a comparative-quantitative approach using data obtained from the Detail Engineering Design (DED), Bill of Quantities (BoQ), and Unit Price Analysis (AHSP). The results show that the conventional method produces higher costs due to generalized volume calculations and excessive tolerances, while the 5D BIM method provides more accurate, efficient, and integrated results since each structural element is calculated automatically through digital modeling. Therefore, the implementation of 5D BIM has proven to enhance accuracy, time efficiency, and overall effectiveness in construction cost planning compared to conventional methods.